2008
DOI: 10.1053/j.ajkd.2008.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and Creatinine in an HIV Cohort: The Nutrition for Healthy Living Study

Abstract: Background-Human immunodeficiency virus (HIV)-infected persons have increased risk of chronic kidney disease (CKD). Serum creatinine may underestimate prevalence of CKD in subjects with decreased lean body mass or liver disease. Serum cystatin C, an alternative kidney function marker, is independent of lean body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 64 publications
8
52
1
3
Order By: Relevance
“…These included the same risks for microalbuminuria as shown in previous studies in Caucasian populations and in the FRAM cohort, namely older age, higher Cr, hypertension, diabetes mellitus, hepatitis C coinfection and hypercholesterolemia [7,9,22,24,26,27]. In addition, our study showed an association between decreasing CD4 count and the presence of renal dysfunction, but no associations between HIV-RNA level and any kidney disease.…”
Section: Discussionsupporting
confidence: 80%
“…These included the same risks for microalbuminuria as shown in previous studies in Caucasian populations and in the FRAM cohort, namely older age, higher Cr, hypertension, diabetes mellitus, hepatitis C coinfection and hypercholesterolemia [7,9,22,24,26,27]. In addition, our study showed an association between decreasing CD4 count and the presence of renal dysfunction, but no associations between HIV-RNA level and any kidney disease.…”
Section: Discussionsupporting
confidence: 80%
“…22 The use of cystatin C is particularly relevant for older populations and for persons with chronic illnesses such as HIV infection. 23,24 Several studies have examined cystatin C as a marker of kidney function in HIVinfected persons [25][26][27] and specifically proposed using serum cystatin C as an alternative marker for renal impairment in this population. In the present analysis, we evaluated renal function of participants in a contemporary cohort of HIVinfected patients treated only with cART or who were antiretroviral naive to describe the prevalence of and risk factors associated with renal dysfunction and to examine the association of elevated cystatin C levels with preclinical renal dysfunction in this population.…”
mentioning
confidence: 99%
“…традиційно для оцінки функції нирок використовують ШкФ, яку розра-ховують на основі ендогенного креатиніну по формулам Cockcroft-Gault або Modification of Diet in Renal Disease (MDRD) [25]. У дослідженні [26] встановлено, що у Віл-інфікованих хворих рівень сироваткового креатиніну був значно нижче, ніж у хворих без Віл-інфекції. У той же час науковці не виявили відмінностей у величині креатиніну крові Віл-серопозитивних і Віл-серонегативних хворих.…”
Section: (84)2016 інфекційні хворобиunclassified
“…(2006) і C. I. Esezobor та ін. (2010) кореляції між кількістю CD4+-лімфоцитів і рівнем сироваткового цистатина С не було виявлено [25][26][27][28][29]. Переваги цистатина С перед креатиніном в оцінці функції нирок при Віл-інфекції було показано а. Bonjoch та ін.…”
Section: (84)2016 інфекційні хворобиunclassified
See 1 more Smart Citation